Moving into meditation: a 12-week mindfulness program for yoga practitioners - Cushman, Anne (Shambhala, 2014)
Machine generated contents note: Introduction -- Part 1: Getting Started -- 1. Mindful Yoga and Embodied Meditation -- 2. A Little Bit of Yoga History -- 3. When, Where, and What to Practice -- Part 2: The Program -- Week 1: Inhabiting Your Body -- Week 2: Exploring Your Body in Action -- Week 3: Getting to Know Your Breath -- Week 4: Cultivating Your Breath -- Week 5: Taking Your Seat: Going Deeper into Seated Meditation Posture -- Week 6: Not Just Standing: Exploring Standing and Walking Meditation -- Week 7: Befriending Our Bodies, Befriending Our World: The Art of Metta in Motion -- Week 8: I Love It, I Hate It: Exploring the Realm of Feeling-Tones -- Week 9: Coming Home to Our Hearts -- Week 10: The Storytelling Mind -- Week 11: Suffering and Freedom -- Week 12: Impermanence and No Separate Self